Nursing Needs Of Patients With Postpartum Depression - Račkauskaitė, Gabrielė; Kuskienė, Milda (Slauga. Mokslas ir praktika, 2020)
Postpartum depression is an inhomogeneous, serious disorder that determines the quality of life and morbidity, which occurs during the most sensitive period of a woman’s life. Postpartum depression has a negative impact not only on the mother, but also on the well-being of her baby and family members. In order to ensure the best possible care for patients suffering from postpartum depression, it is necessary to identify and meet their care needs. For a holistic assessment of nursing needs, it is recommended to consider 12 vital activities (according to N. Roper’s Nursing model). In order to solve the nursing problems of patients with postpartum depression, it is necessary to meet their nursing needs. The research tool - questionnaires for patients with postpartum depression and nurses caring for them - was compiled by the author of the research after the analysis of the scientific medical literature on the topic. Evaluating the data of the study, it can be stated that specialized, holistic care is necessary for patients with postpartum depression. For them, nursing problems are identified in all vital activities. Vital activities of communication, employment and sleep are particularly affected. In the care of women with postpartum depression, not only the treatment prescribed by a doctor is used, but communication and psychological support are very important. Positive results were obtained after assessing the satisfaction of the patients who participated in the survey with their nursing.
Keywords: nursing; depression; vital activities; postnatal period